Socialization and Education on the Use of Temulawak (Curcuma xanthorriza) in Increasing Immunity in Palembang - Hidayat, Rachmat; Wulandari, Patricia (HM Publisher, 2021)
The Palembang community are still unfamiliar with and do not know the use of medicinal plants, one of which is curcuma in improving the quality of health, in this case, increasing immunity. This study aimed to describe community service in the form of socialization and education regarding the use of temulawak to increase body immunity in the Palembang community. This community socialization and education activity was held through online meetings using Google Meet every week during May 2020. The meetings were held 4 times, with each meeting duration of 2 hours. The material for the meeting included the introduction of herbal plants, which have the effect of increasing immunity, the introduction of the ginger plant and its properties, and the processing of temulawak into a healthy drink. This activity was attended by 154 participants consisting of the general public and health workers in the working area of the Campus Health Center, South Sumatra. In conclusion, socialization and educational activities on the use of medicinal plants, especially by academicians, are very much needed by the community. Activities like this are very important to improve the health status and resilience of natural-based communities around us.